Periodic dynamic systems for infected hosts and mosquitoes Sistemas dinâmicos periódicos para hospedeiros e mosquitos infectados - W. M. Oliva; E. M. Sallum (Universidade de São Paulo, 1996)
A mathematical model for the purpose of analysing the dynamic of the populations of infected hosts anf infected mosquitoes when the populations of mosquitoes are periodic in time is here presented. By the computation of a parameter lambda (the spectral radius of a certain monodromy matrix) one can state that either the infection peters out naturally) (lambda <= 1) or if lambda > 1 the infection becomes endemic. The model generalizes previous models for malaria by considering the case of periodic coefficients; it is also a variation of that for gonorrhea. The main motivation for the consideration of this present model was the recent studies on mosquitoes at an experimental rice irrigation system, in the South-Eastern region of Brazil. Desenvolveu-se um modelo matemático para analisar a dinâmica das populações de indivíduos e mosquitos infectados quando as populações de mosquitos são periódicas no tempo. Pela determinação de um parâmetro lambda (o raio espectral de uma matriz de monodromia) pode-se estabelecer que a infecção termina naturalmente (lambda <= 1) ou se lambda > 1 que a infecção torna-se endêmica. O modelo generaliza, para o caso de coeficientes periódicos, modelos anteriores para malária; como também é uma variação de modelo para a gonorréia. A principal motivação para a consideração do modelo proposto foram os recentes estudos sobre mosquitos numa estação experimental de arroz irrigado, na região Sudeste do Brasil.